THE RELATIONSHIP BETWEEN SELF CONFIDENCE AND STUDENT’S SKILL IN READING ANALYTICAL EXPOSITION TEXT AT THE ELEVENTH GRADE OF SMAN 11 JAMBI CITY - Sakinah, Nina; Fitri, Nurul; Silfia, Efa (Universitas Batanghari Jambi, 2026)
Reading skills are one of the fundamental competencies essential to the learning process, particularly in secondary education. At the high school level, students are expected not only to read but also to comprehend and analyze complex texts, such as analytical exposition texts. However, reading ability is influenced not only by cognitive factors but also by psychological aspects, including self-confidence. This study aims to examine the relationship between students’ self-confidence and their reading skills in analytical exposition texts. The research was conducted using a quantitative approach with a correlational design involving students of class XI F8 at SMAN 11 Jambi City. Data were collected through a self-confidence questionnaire and a reading comprehension test. The results revealed a moderate correlation between self-confidence and reading skill, with a correlation coefficient of 0.574. However, self-confidence only accounted for 10.7% of the variance in reading scores, indicating that other factors, such as vocabulary mastery, reading strategies, and learning environment, play a more significant role. These findings suggest the need for a holistic approach in improving students’ reading skills by not only enhancing self-confidence but also incorporating effective reading strategies and supportive learning environments